2010
DOI: 10.1001/archinternmed.2010.17
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in Chronic Obstructive Pulmonary Disease Prevalence, Incidence, and Mortality in Ontario, Canada, 1996 to 2007

Abstract: Our findings indicate a substantial increase in COPD prevalence in the last decade, with more of the burden being shifted from men to women. Effective clinical and public health strategies are needed to prevent COPD and manage the increasing number of people living longer with this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
120
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 21 publications
19
120
1
5
Order By: Relevance
“…[10][11][12] However, COPD is primarily managed within the primary care sector. The Canadian Primary Care Sentinel Surveillance Network was established in 2008 to bring together practice-based research networks using diverse EMR systems to generate data on chronic disease in Canadian primary care settings.…”
Section: Cmaj Openmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] However, COPD is primarily managed within the primary care sector. The Canadian Primary Care Sentinel Surveillance Network was established in 2008 to bring together practice-based research networks using diverse EMR systems to generate data on chronic disease in Canadian primary care settings.…”
Section: Cmaj Openmentioning
confidence: 99%
“…16 This may explain in part the significant differences between the rates observed in our data and the prevalence of almost 12% in adults over age 35 reported most recently by Gershon and colleagues. 10,26 The true prevalence is likely found between these levels. A recent study by Muggah and colleagues 27 also showed poor agreement between data from a large population health survey and the administrative data definition used in Ontario (κ = 0.29, prevalence 11.1% health administrative data, 5.6% selfreported).…”
Section: Cmaj Openmentioning
confidence: 99%
“…We are unable to comment on whether anxiety or depression had improved substantially for patients after opioids were started, but caregivers often mentioned that their loved one appeared "more relaxed." We did not collect spirometric measures of airflow obstruction (i.e., FEV 1 or FEV 1 /FVC ratio); most of the included patients were housebound, living with high dyspnea burden and had not undergone recent pulmonary function testing.…”
Section: Limitationsmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease is an increasing health issue worldwide [1][2][3][4][5] and is expected to be the third leading cause of death by 2020 [6,7] . Similarly, the World Health Organization [8] reports that COPD is the fifth most common cause of death and the tenth most burdensome disease worldwide.…”
Section: Introductionmentioning
confidence: 99%